Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

let $f(0)=1$ and $f'(0)=1$.

and $f(x+y)=f(x)f(y)$ for $x,y\in R$.

How can I found $f(x)$ by using a definition of derivative?

share|improve this question
    
What have you tried? And how could you use the definition of the derivative here to learn more about $f$? –  TMM Sep 15 '11 at 13:34
    
$f(x+h)=f(x)f(h)$, $f(x+h)-f(h)=f(x)(f(h)-1)$, $\frac{f(x+h)-f(h)}{h}=f(x)\frac{f(h)-1}{h}$, $\lim_{h\to 0}$, then $f'(x)=f(x)$ –  4545454545SI Sep 15 '11 at 13:39
    
If you get $f'(x) = f(x)$ you're done? –  TMM Sep 15 '11 at 13:42
3  
Well you can already show $f'=f$ and you know $f(0)=1 $so now can you prove that $ e^x $ is the unique solution to that Initial value problem? Hint: Assume $y=e^x g(x)$ solves the IVP and plug it in to see if you can say anything about what $g$ must be. –  Ragib Zaman Sep 15 '11 at 13:46
3  
If $f'(x) = f(x)$, then $f'(x) / f(x) = 1$. But $f'(x)/f(x) = \frac{d}{dx} \ln(f(x)) = 1$ implies $\ln(f(x)) = x + C$ and $f(x) = D e^x$. If of course you are allowed to use all that. –  TMM Sep 15 '11 at 13:47

1 Answer 1

up vote 4 down vote accepted

Let me just turn that last comment into an answer. As you already pointed out in the comments, by the definition of the derivative and using $f(x+y) = f(x)f(y)$, $f(0) = 1$ and $f'(0) = 1$ we have

$$f'(x) = \lim_{h\to 0} \frac{f(x+h)-f(x)}{h} = \lim_{h\to 0} \frac{f(x)f(h)-f(x)f(0)}{h} = f(x) \lim_{h\to 0} \frac{f(h)-f(0)}{h} = f(x) f'(0) = f(x)$$

Now you're almost done, as $f'(x) = f(x)$ is one of the essential properties of the exponential function. From $f'(x) = f(x)$ it follows that

$$\frac{f'(x)}{f(x)} = \frac{d}{dx}\left(\ln f(x)\right) = 1$$

Integrating both sides, we get $\ln f(x) = x + C$ for some constant $C$. This implies $f(x) = D e^x$ for some constant $D$ (i.e. $D = e^C$). We know that $f(0) = 1$, so it follows that $D = 1$ and $f(x) = e^x$.

Alternatively, as pointed out by Ragib, after noticing $f'(x) = f(x)$ you could write $f(x) = e^x g(x)$ for some function $g(x)$. Then $f'(x) = e^x g'(x) + f(x) = f(x)$, so $e^x g'(x) = 0$ for all $x$. Since $e^x \neq 0$, it follows that $g'(x) = 0$ and $g(x) = D$ is constant. Using $f(0) = 1$ it then follows that $D = 1$ and $f(x) = e^x$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.